Antioxidants in heat-processed koji and the production mechanisms. (15th November 2015) - Okutsu, Kayu; Yoshizaki, Yumiko; Ikeda, Natsumi; Kusano, Tatsuro; Hashimoto, Fumio; Takamine, Kazunori
Highlights: Two furan derivatives were identified as the antioxidants in heat-processed koji. The antioxidants were not present in intact koji and formed by heating. They were effectively formed by two-step heating (55 °C/2 days → 75 °C/3 days). Isomaltose was a precursor of 5-(α-d -glucopyranosyloxymethyl)-2-furfural. Abstract: We previously developed antioxidative heat-processed (HP)-koji via two-step heating (55 °C/2 days → 75 °C/3 days) of white-koji . In this study, we isolated antioxidants in HP-koji and investigated their formation mechanisms. The antioxidants were identified to be 5-hydroxymethyl furfural (HMF) and 5-(α-d -glucopyranosyloxymethyl)-2-furfural (GMF) based on nuclear magnetic resonance spectral analysis. HMF and GMF were not present in intact koji, but were formed by heating at 75 °C. As production of these antioxidants was more effective by two-step heating than by constant heating at 55 °C or 75 °C, we presumed that the antioxidant precursors are derived enzymatically at 55 °C and that the antioxidants are formed subsequently by thermal reaction at 75 °C. The heating assay of saccharide solutions revealed glucose and isomaltose as HMF and GMF precursors, respectively, and thus the novel finding of GMF formation from isomaltose. Finally, HMF and GMF were effectively formed by two-step heating from glucose and isomaltose present in koji.